The apple doesn't fall far from the tree: location of start-ups relative to incumbents - Oliver Falck; Michael Fritsch; Stephan Heblich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
New firm location decisions, relative to incumbents may be based on a choice between two types of advantages: natural advantages or those that arise from social embeddedness, the latter of which may particularly include knowledge spillovers. We analyze the relative importance of geographically bounded location factors based on data from 103 manufacturing industries across 327 West German and 111 East German districts. Our micro-geographic analysis reveals that the two parts of the country vary in their pattern of new firm location. In East Germany, only 5 percent of the industries reveal start-up localization patterns beyond what natural advantages would suggest compared to 40 percent in West Germany.
Keywords: L26; R11; O18; 330; Entrepreneurship; location decision; natural advantages; local knowledge spillovers; Unternehmensgründung; Standort; Standortfaktor; Spillover-Effekt; Industriegeographie; Alte Bundesländer; Neue Bundesländer; Deutschland